Negotiating polyvocal strategies: Re-reading de Certeau through the lens of urban planning in South Africa. (September 2020) - Andres, Lauren; Jones, Phil; Denoon-Stevens, Stuart Paul; Lorena, Melgaço
The Practice of Everyday Life (de Certeau M (1984) The Practice of Everyday Life. Berkeley, CA: University of California Press) has become a canonical text in urban studies, with de Certeau's idea of tactics having been widely deployed to understand and theorise the everyday. Tactics of resistance were contrasted with the strategies of the powerful, but the ways in which these strategies are operationalised were left ambiguous by de Certeau and have remained undertheorised since. We address this lacuna through an examination of the planning profession in South Africa as a lieu propre – a strategic territory with considerable power to shape urban environments. Based on a large interview data set examining practitioner attitudes toward the state of the profession in South Africa, this paper argues that the strategies of the powerful are themselves subject to negotiation. We trace connections with de Certeau's earlier work to critique the idea that strategies are univocal. We do this by examining how the interests of different powerful actors can come into conflict, using the planning profession as an exemplar of how opposing strategies must be mediated in order to secure changes in society.